PERBANDINGAN KONSEP METAFISIKA IMAM AL-GHAZALI DAN SEYYED HOSSEIN NASR - Rusiah; Abu Anwar (STAI Nurul Falah Airmolek, 2023)
This article aims to discuss a comparison of metaphysical concepts between Imam Al-Ghazali and Seyyed Hossein Nasr, two great thinkers in the Islamic philosophical tradition who made significant contributions to understanding the nature of reality and the relationship between God and the universe. This research uses a descriptive qualitative research library approach. The results of the analysis show that Imam Al-Ghazali, in his works such as Tahafut al-Falasifah, criticized the rationalism of Greek philosophers and emphasized the limitations of human reason in understanding God, while proposing the concept of the world as God's creation which is continuously renewed by His will. In contrast, Seyyed Hossein Nasr developed a metaphysical approach that combines elements of Islamic mysticism and perennialist philosophy, viewing the universe as a manifestation of the infinite reality of God and emphasizing the unity between science and spirituality. Both figures agree that metaphysical pursuits must involve deep spiritual understanding, although their methods and approaches differ